Penguatan Moderasi Beragama dan Pemberdayaan UMKM Sebagai Strategi Penurunan Kemiskinan Ekstrem di Desa Tanah Merah Kecamatan Perbaungan - Zainarti Zainarti; Wahid Luthfi Hakim; Ade Fahdiya Syakhilah; Tasya Fadilah; Nadia Zahra Hasibuan (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Community Service Program (KKN) is one of the implementations of the Tri Dharma Perguruan Tinggi (Three Pillars of Higher Education) which requires students to make a real contribution to society, particularly in strengthening religious moderation and empowering MSMEs in Tanah Merah Village, Perbaungan District, Serdang Bedagai Regency, which faces the challenge of extreme poverty due to the weakening of local economic activity following the construction of a toll road. This study aims to describe and analyze the role of students from the Community Service Program of the State Islamic University of North Sumatra (UINSU) in implementing a spiritual strengthening program based on religious moderation and economic empowerment through MSMEs. The method used is descriptive qualitative with purposive sampling techniques, involving MSME actors, PKK mothers, perwiritan mothers, and MIS students as program targets. Data was obtained through participatory observation, interviews, discussions, and field documentation. The results of the community service showed that the tahsin and perwiritan programs succeeded in strengthening the understanding of inclusive religious moderation, while the empowerment of MSMEs through digital branding, entrepreneurship training, and product innovation such as LEMONERA liquid soap was able to increase local business capacity and open up new economic opportunities. In conclusion, the integration of religious moderation and MSME empowerment has proven to be an effective strategy for reducing extreme poverty, as it not only improves economic resilience but also strengthens social and spiritual cohesion within the community in a sustainable manner.